2017
DOI: 10.1002/brb3.757
|View full text |Cite
|
Sign up to set email alerts
|

Recruitment of orbitofrontal cortex during unpredictable threat among adults at risk for affective disorders

Abstract: Background: Mood and anxiety disorders are characterized by altered prefrontal-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 55 publications
(71 reference statements)
0
9
0
Order By: Relevance
“…Human functional magnetic resonance imaging (fMRI) studies have reported BNST activation to uncertain threat anticipation [27][28][29][30][31][32] , yet evidence that the BNST encodes subjective anticipatory experience remains controversial. Previous fMRI studies comparing conditions of uncertain threat versus safe anticipation (overview see 33 ) have revealed increased activity in a broad range of brain regions such as BNST 30,31,34,35 , amygdala [36][37][38] , periaqueductal gray (PAG) 29,34,39 , anterior insula (aINS) [27][28][29]40,41 , anterior cingulate cortex (ACC) 28,29,40,42,43 and lateral and medial frontal regions 41,[44][45][46] . However, the comparison does not allow to specifically isolate the subjective feeling of uncertain threat anticipation given that the conditions may differ in several other mental processes (e.g., defensive responses or arousal), and the identified regions are involved in fundamental cognitive processes including salience or arousal 13 .…”
Section: Introductionmentioning
confidence: 99%
“…Human functional magnetic resonance imaging (fMRI) studies have reported BNST activation to uncertain threat anticipation [27][28][29][30][31][32] , yet evidence that the BNST encodes subjective anticipatory experience remains controversial. Previous fMRI studies comparing conditions of uncertain threat versus safe anticipation (overview see 33 ) have revealed increased activity in a broad range of brain regions such as BNST 30,31,34,35 , amygdala [36][37][38] , periaqueductal gray (PAG) 29,34,39 , anterior insula (aINS) [27][28][29]40,41 , anterior cingulate cortex (ACC) 28,29,40,42,43 and lateral and medial frontal regions 41,[44][45][46] . However, the comparison does not allow to specifically isolate the subjective feeling of uncertain threat anticipation given that the conditions may differ in several other mental processes (e.g., defensive responses or arousal), and the identified regions are involved in fundamental cognitive processes including salience or arousal 13 .…”
Section: Introductionmentioning
confidence: 99%
“…The OFC chiefly influences purposeful actions via the rewarding aspects of reinforcers and correlates with subjective emotional experiences; when OFC is impaired, patients use the inability to perceive changes in physical state as a warning cue to control unwanted behavior, while ceasing to perform in response to incentive or punishment predictions and reducing purposeful actions ( Rudebeck and Rich, 2018 ; Rolls, 2019 ). Abnormalities within the OFC are observed in a range of mental diseases, such as bipolar condition ( Ferguson and Gao, 2018 ), depression ( Lai, 2021 ), anxiety conditions ( Kirlic et al, 2017 ), obsessive-compulsive syndrome ( Nakao et al, 2014 ), social interaction problems ( Evans et al, 2004 ), and conditions involving drug misuse Stoeckel et al (2015) demonstrated a correlation between the OFC and the habituation of breathlessness perception in asthma patients. Herigstad et al (2017) also found that the OFC played a part in the heightened sensitivity of dyspnea in patients with COPD who were participating in breathing therapy.…”
Section: Discussionmentioning
confidence: 99%
“…An example for such an anxiety-induction procedure is the threat of shock paradigm, which induces sustained anxiety by informing participants that they will receive unpleasant electrical stimuli during the experiment (e.g., 64 68 ). For example, Kirlic, et al (2017) 69 demonstrated that participants with high risk for affective disorder display less exploratory behavior in response to a threat of shock. Using this paradigm in the OFT would offer the possibility to investigate the effects of state anxiety on thigmotaxis as a defensive behavior.…”
Section: Discussionmentioning
confidence: 99%